Human Trafficking Policy Implementation : The Impact of Crime Rate on Instability Tourist Arrivals in Perlis (International Journal of Psychosocial Rehabilitation, 2020)
Safety is a critical issue that every tourist is considering and bearing in mind before traveling to a country. Crime commonly happening in the city area is a major issue for tourists when debating security issues in urban tourism. In 2015, Malaysian police discovered 139 graves of human trafficking victims in 28 detention camps in the jungle of Perlis near the Thai border. Tourism sector performance contributes to a large part of the Malaysian service economy (The World Factbook, 2013). Recently, data from the Ministry of Tourism, Arts, and Culture (MOTAC) have revealed that the number of tourists decreased by 1.5% in 2018. Malaysia encountered an economic crisis in 2016, and it affected tourism sectors. This situation has become a serious issue for the government because the tourism sector is one of the government’s important agendas in the NKEAs through the National Ecotourism Plan. However, an unsafe country can lead to adverse tourist arrival impacts. Thus, this research attempts to investigate the impacts of crime on instability in tourist arrivals in Perlis, Malaysia. Therefore, tourists are the primary respondents in this study, as the aim of this study involves tourist perceptions on the importance and performance of crime prevention measures in the safety issues to enhance tourist numbers. However, through this research, the researcher can see such measures as awareness of the public getting the lowest ranking. Findings reveal the authorities should address the problem and take the opportunity to further enhance the level of awareness of the community and tourists about the safety issues. This study shows that the result of Pearson chi-square = 25.202, p = 0.001. This tells us that there is a significant association between human trafficking and tourist arrivals. All tourists have a high and moderate perception of the human trafficking crime aspect regarding Perlis. Phi and Cramer’s V are both tests of the strength of association. It is important to realize that this result captures the bigger issues related to the agreement level among those who gave positive responses towards these human trafficking issues, which was at the above-average scale with a mean score of 3.65 (of a 5-point Likert scale). To point out, the current study shows more than half of the respondents (58.47%) with the highest confidence level (mean of 3.65) voted that human trafficking will bring the possible tourist not to come to Perlis.